Digital Leadership as a Catalyst for Community-Based Smart Tourism Development: Advancing Sustainable Tourism Destinations - Hamdan Hamdan; M. Rizky Mahaputra; M. Ridho Mahaputra (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2026)
This study examines the role of digital leadership as a catalyst for community-based smart tourism development toward sustainable tourism destinations. A quantitative approach with a causal research design was employed, involving 42 tourism village managers in West Lombok Regency, Indonesia. Data were collected through a structured questionnaire and analyzed using PLS. The findings reveal that digital leadership positively influences sustainable community-based smart tourism development. Specifically, technology awareness, digital ethics, digital change management, digital knowledge sharing, and digital risk awareness strengthen managers’ capabilities to identify challenges, develop innovative solutions, promote new ideas, and implement innovation. These capabilities enhance the adaptive capacity and competitiveness of tourism villages while supporting long-term sustainability. This study contributes to the growing smart tourism literature by demonstrating that digital leadership is a strategic organizational capability for fostering innovation-driven, community-based, and sustainable tourism destination development.